Evaluation of analytical footprint models and energy balance closure methods over cotton in Texas panhandle - Joy, Stuart L., author; Chávez, José Luis, advisor; Ham, Jay, committee member; Andales, Allan A., committee member (Colorado State University. Libraries, 2011)
Eddy covariance (EC) systems are being used to measure sensible heat (H) and latent heat (LE) fluxes in order to determine crop water use or evapotranspiration (ET). However, EC systems tend to systematically underestimate H and LE fluxes; thus, a lack of energy balance closure. The reliability of EC measurements depends on meeting certain meteorological assumptions; the most important of such are a horizontal homogeneity, stationarity, and non-advective conditions. Over heterogeneous surfaces the spatial context of the measurement must be known in order to properly interpret the magnitude of the heat flux measurement results. Over the past two decades there has been a proliferation of `heat flux source area' (i.e., footprint) modeling studies but only a few that explore the accuracy of models over heterogeneous agricultural land. A composite ET estimate was created by using the estimated footprint weights for an EC system in the upwind corner of four fields and separate ET estimates from each of these fields. Three analytical footprint models were evaluated by comparing the composite ET to the measured ET. All three models performed consistently with an average MBE of about -0.03 mm h-1 (-4.4%) and RMSE of 0.09 mm h-1 (10.9%). The same three footprint models were then used to adjust measured ET to account for the fraction of the footprint that extended beyond the field of interest. The effectiveness of the footprint adjustment was determined by comparing adjusted ET estimates with lysimetric ET measurements from within the same field. This correction decreased the absolute hourly ET MBE by 8% and the RMSE by 1%. The energy balance is rarely closed with the EC method and therefore the energy balance was closed by adjusting the H and LE heat fluxes by first assuming the H was measured accurately and applying the entire residual to the LE (LEC) heat flux and secondly by assuming the Bowen ratio (BRC) was measured accurately and adjusting both H and LE while conserving the BR. The application of energy balance closure to uncorrected EC heat fluxes showed better agreement between EC and lysimeter ET. There was not a significant difference between the BRC and LEC methods when applied to uncorrected heat fluxes. The analytical footprint models developed by Schuepp et al. (1990), Hsieh et al. (2000), and Kormann and Meixner (2001) all gave a reliable estimate of the footprint for heterogeneous agricultural land under highly advective conditions. Care should be taken when using the EC system to measure ET early in the growth stage of a crop when the surface is smooth because the footprint will extend farther upwind. Correcting the EC heat fluxes for coordinate rotation, density, spectral attenuation, and sonic temperature heat flux and then applying the proposed correction considering the footprint resulted in the most accurate estimate of hourly EC based ET with a MBE of 0.01 mm h-1 (0.6 to 1.5%) and RMSE of 0.10 to 0.11 mm h-1 (10.6 to 11.66%).
Keywords: cotton; footprint; evapotranspiration; energy balance closure; eddy covariance